Early anthropological discourse on the Inuit and the influence of Virchow on Boas - Baehre, Rainer (Études/Inuit/Studies, 2008)
AbstractThis article examines the anthropological context of Rudolf Virchow’s study of two Labrador Inuit families displayed at an 1880 Völkerschau (‘ethnographic exhibit’) in Berlin, and how the latter reflected the ongoing discourse of the Inuit as a “race.” It also discusses how Virchow’s anthropometrical methodology and findings regarding the two families are linked to Franz Boas’ Arctic fieldwork and subsequent anthropological research. Virchow, one of the founders of German ethnology and anthropology, had contributed to a sparse “scientific” discourse surrounding the “Esquimaux” with several studies on Arctic peoples, before meeting the young Boas. In particular, this Völkerschau provided him with the unprecedented opportunity of studying the Labrador Inuit directly. An analysis of his study, and other work by Virchow, sheds light on the contemporary issues of anthropological interpretation, which he faced, and how his approach lent itself to the choice of Baffin Island by Boas as a site of fieldwork, as well as the shift towards cultural relativism.